Social Protection in Latin America Causality, Stratification and Outcomes - Barrientos, Armando; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book offers a comprehensive analysis of social protection in Latin America, its origins, institutions, and outcomes. The chapters are organised in three groups. The earlier chapters discuss in turn appropriate methods, an analytical framework, and core institutions. The book advocates a causal inference approach to the study of the institutions that have dominated social protection in the region: occupational insurance, individual retirement savings, and social assistance. The middle chapters study social protection$1 (Bs main stratification effects, focussing on stratification effects on employment, protection, and worker incorporation. The later chapters then assess social protection outcomes and identify country groupings including their evolution over time. The book, and its approach and findings, contributes to the advancement of a theory of social protection amongst late industrialisers. Armando Barrientos is Professor Emeritus of Poverty and Social Justice at the Global Development Institute at the University of Manchester, UK. He was Research Director at the World Poverty Institute. .s
Chapter 1. Introduction -- Chapter 2. Methods -- Chapter 3. Framework -- Chapter 4. Institutions -- Chapter 5. Employment -- Chapter 6. Protection -- Chapter 7. Incorporation -- Chapter 8. Clusters -- Chapter 9. Conclusion.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Social policy; Social choice; Welfare economics; Political sociology; Social Policy; Comparative Social Policy; Social Choice and Welfare; Political Sociology